Exposure-response models based on extended follow-up of a cohort mortality study in the automobile industry - Eisen, Ellen A; Bardin, Judith; Gore, Rebecca; Woskie, Susan R; Hallock, Marilyn F; Monson, Richard R (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'This report describes the extended follow-up of a cohort of 46 399 automobile manufacturing workers with potential exposure to metalworking fluids (MWF). The outcomes of interest were cancers of the esophagus, stomach, colon, rectum, liver, pancreas, larynx, skin, prostate, and brain, as well as leukemia. Additional follow-up increased the power to detect modest elevations in mortality rates in association with specific types of MWF, including synthetic fluids not in widespread use until the 1970s. ' ' METHODS ': 'Standardized mortality ratios (SMR) were computed for the most recent 10 years of follow-up, as well as for the entire study period. Adjusted relative risks (RR) were estimated in Poisson regression models with categorical variables for cumulative exposure to each type of MWF and in proportional hazards models with continuous exposure variables. ' ' RESULTS ': 'Associations were found between straight MWF and esophageal, laryngeal and rectal cancer; soluble MWF and cancer of the esophagus, larynx, skin, and brain; synthetic MWF and cancer of the esophagus, liver, and prostate. The elevated RR values were modest in magnitude (1.5 to 2.0). SMR values were increased for stomach, liver, and pancreatic cancer and also for leukemia in the last 10 years of follow-up. The SMR values were also elevated for stomach and liver cancer among the persons recently hired. ' ' CONCLUSIONS ': 'The results provide further evidence that exposure to metalworking fluids causes cancer among workers in automobile manufacturing. Although airborne exposures declined over the study period, this study suggests that modest risk of several digestive cancers, as well as prostatic cancer and leukemia, may persist at current levels of exposure to water-based metalworking fluids.
Keywords: automobile industry; cancer; case-cohort study; cohort mortality study; exposure-response model; extended follow-up; metalworking fluid; proportional hazards model